How do octopi eat pizza pie? : pizza math. (Alexandria, Virginia : Time Life for Children, 1992)
A collection of stories, poems, games, and activities, all focusing on food, introduce such basic mathematical skills as number awareness, addition, subtraction, and estimation.
Keywords: Mathematics-Juvenile literature; Food--Juvenile literature; Mathematical recreations; Food--Miscellanea